PENEGAKAN HUKUM TERHADAP ILLEGAL LOGGING DI INDONESIA DITINJAU DARI PERSPEKTIF HUKUM PIDANA - Yeyen Andrizal (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2019)
As we all know that in the current era of development, each country is demanded to be able to increase development in order to catch up or equal the countries that are considered established in order to sustain international stability. The development is specifically directed towards realizing just and prosperous community welfare in each country, including Indonesia, with regard to all aspects including the environmental aspects, as explained in article 33 paragraph 3 of the 1945 Constitution as a constitutional foundation, namely: